Interplay of Endogenous Resources and Exogenous Forces in Driving Strategic Agility: A Mixed-Methods Study - Elezaj, Elvis (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Contemporary business environments are characterized by increasing complexity and rapid change, positioning strategic agility as a critical driver of organizational resilience and sustainable success. Study examines strategic agility through an integrative endogenous–exogenous analytical lens, offering a theoretically grounded and empirically robust investigation of how leaders navigate complexity by aligning internal capabilities with external environmental dynamics. Employing a mixed-methods design, study draws on evidence from 100 case studies and integrates quantitative metrics with qualitative insights through the Delphi method, enabling a systematic exploration. This approach facilitates in-depth examination of the interplay between firm-level resources, environmental pressures, and strategic decision-making. Findings indicate that leaders systematically engages endogenous–exogenous (Endo–Exo) analysis exhibit an enhanced capacity to anticipate change, leverage competitive advantages, and foster adaptive organizational cultures. Results further demonstrate a strong association between Endo–Exo analysis and improved strategic coherence, organizational agility, and leadership effectiveness. Research contributes a robust analytical framework for strategic leadership that is both theoretically rigorous and practically relevant within dynamic and uncertain organizational contexts.